Perlindungan Hukum Terhadap Peralihan Hak Cipta Menurut Undang-Undang Hak Cipta No. 28 Tahun 2014 - Rachman, Tasya Putri; Yunanto, Yunanto (UNES Law Review, 2023)
Universally it can be stated that the objects that have been determined by IPR are various works that appear or are born due to the ability of human thinking. This research aims to find out whether the UUHC has provided protection against the transfer of copyright and to find out the validity period of this protection as well as sanctions for people who violate copyright. The research method used is normative juridical. The source and type of research data is primary legal material based on Law Number 28 of 2014 concerning Copyright and other related laws and regulations. Secondary legal materials consist of research results and books related to this article and tertiary legal materials consist of legal dictionaries and the internet. The data collection method in this juridical-nomative research requires secondary data with primary, secondary, tertiary and other legal materials. This data was obtained from literature or document studies. The results of the research concluded that the “UUHC has provided protection for inventors and given special rights that are closely related to the creations produced. There are three ways that can be done to resolve disputes regarding Article 95 of the UUHC through court, through arbitration, or through alternative dispute resolution.